1990
DOI: 10.1172/jci114819
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I and its amphipathic helix peptide analogues inhibit human immunodeficiency virus-induced syncytium formation.

Abstract: The envelope (membrane) glycoprotein of HIV is essential for virus attachment and entry into host cells. Additionally, when expressed on the plasma membrane of infected cells, the envelope protein is responsible for mediating cell-cell fusion which leads to the formation of multinucleated giant cells, one of the major cytopathic effects of HIV infections. The envelope glycoproteins of HIV contain regions that can fold into amphipathic alpha-helixes, and these regions have been suggested to play a role in subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 34 publications
2
42
3
Order By: Relevance
“…These results demonstrate that D-4F may be acting through multiple pathways. Taken together with previous reports, 4,11,15,[22][23][24] our results suggest that apoA-I and apoA-I mimetic peptides such as D-4F are potent antiinflammatory agents that may have therapeutic potential.…”
Section: Van Lenten Et Al D-4f Inhibits Influenza-induced Macrophage supporting
confidence: 88%
See 1 more Smart Citation
“…These results demonstrate that D-4F may be acting through multiple pathways. Taken together with previous reports, 4,11,15,[22][23][24] our results suggest that apoA-I and apoA-I mimetic peptides such as D-4F are potent antiinflammatory agents that may have therapeutic potential.…”
Section: Van Lenten Et Al D-4f Inhibits Influenza-induced Macrophage supporting
confidence: 88%
“…Based on previous studies in vitro, 23,24 we measured viral titers in lungs from PBS-or D-4F-treated mice before and at 6 macrophages from male donors. At euthanasia, heart was perfused, aortic arch and innominate artery were removed by dissection, and contents of Sry DNA were determined as described in Methods.…”
Section: D-4f Has Antiviral Activitymentioning
confidence: 99%
“…Zangerle et al reported a decrease in HDL in patients CD4 count \ 500, while no difference in others plasma lipids were seen. A high level of HDL may be protective against HIV, since apo A1, the main lipoprotein of HDL, inhibits syncytium formation [35]. In our study, LDL-C shows no correlation with CD4 counts or clinical staging.…”
Section: Discussioncontrasting
confidence: 64%
“…These include New Castle disease virus, Rabies virus, Vesicular stomatitis virus, Japanese encephalitis virus, Rubella virus, Epstein-Barr virus, Herpes simplex virus, HIV, Simian immunodeficiency virus, Xenotropic virus, Sindbis virus, Vaccinia virus, Coxsackie virus, Poliovirus, and Mengo virus (345)(346)(347)(348)(349)(350)(351)(352)(353)(354)(355)(356). VLDL and LDL are particularly active against certain viruses, such as togaviruses (Japanese encephalitis virus and Rubella virus) and rhabdoviruses (Rabies virus and Vesicular stomatitis virus), whereas HDL displays a broader antiviral activity (347,349,356).…”
Section: Lipoproteins Lipoprotein Receptors and Virusesmentioning
confidence: 99%